(untitled) (Texas Journal of Engineering and Technology, 2022)
The sun is the source of all energy on Earth. In temperate climates, 25-30% of the total energy consumed is used for heating, hit water supply and air conditioning. Solar energy is very convenient is supplying energy to remote and low energy facilities. Solar photovoltaics is one of the unconventional and renewable types of energy the converts solar optical radiation energy into electricity and provides consumcts with electricity